Suppression the Leakage of Optical Field and Carriers in GaN-Based Laser Diodes by Using InGaN Barrier Layers - Jing Yang; Degang Zhao; Zongshum Liu; De-Sheng Jiang; Jianjun Zhu; Ping Chen; Feng Liang; S. T. Liu; Wei Liu; Yao Xing; Mo Li (IEEE Photonics Journal)
GaN-based laser diodes (LDs) with different barrier layers are investigated by using simulation and experimental methods. it is found that the absorption loss always decreases with the increasing indium content of the InGaN barrier layer in InGaN/InGaN multiquantum well (MQW) LDs, It leads to an increase of slope efficiency and output power of LDs due to the better optical confinement effect of laser beam. However, when the barrier layer changes from InGaN to AlGaN, both threshold current and slope efficiency deteriorate seriously. Except for the increase of the optical absorption loss resulting from the leakage of the optical field, a large leakage of carriers due to the increased piezoelectric polarization field in InGaN/AlGaN MQW region may also be responsible for this deterioration. Therefore, suppressing the leakage of the optical field and carriers by using relatively higher In content InGaN barrier layer is benefit for obtaining high-performance LDs with low threshold current and high output power.